2014
DOI: 10.1371/journal.pone.0096798
|View full text |Cite
|
Sign up to set email alerts
|

Depth and Medium-Scale Spatial Processes Influence Fish Assemblage Structure of Unconsolidated Habitats in a Subtropical Marine Park

Abstract: Where biological datasets are spatially limited, abiotic surrogates have been advocated to inform objective planning for Marine Protected Areas. However, this approach assumes close correlation between abiotic and biotic patterns. The Solitary Islands Marine Park, northern NSW, Australia, currently uses a habitat classification system (HCS) to assist with planning, but this is based only on data for reefs. We used Baited Remote Underwater Videos (BRUVs) to survey fish assemblages of unconsolidated substrata at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 64 publications
3
20
0
Order By: Relevance
“…As found in similar studies ([34,43,44] and references therein), depth was the variable that contributed most to structure fish assemblages In agreement with these findings, the present research, supported by multivariate analysis, revealed significant differences among fish assemblages associated with different depth layers. However, the separation among groups in the MDS was not always so well defined, (indicating gradual changes in species composition) probably because many fish species, especially deepest ones, showed broad and overlapping depth ranges.…”
Section: Discussionsupporting
confidence: 92%
“…As found in similar studies ([34,43,44] and references therein), depth was the variable that contributed most to structure fish assemblages In agreement with these findings, the present research, supported by multivariate analysis, revealed significant differences among fish assemblages associated with different depth layers. However, the separation among groups in the MDS was not always so well defined, (indicating gradual changes in species composition) probably because many fish species, especially deepest ones, showed broad and overlapping depth ranges.…”
Section: Discussionsupporting
confidence: 92%
“…Depth was the second predictor included in both models. Reef fish communities vary dramatically with depth (Friedlander et al 2010;Schultz et al 2014;Jankowski et al 2015), as predator abundances and species compositions change (Asher et al 2017;Tuya et al 2017). Its inclusion in both models is further evidence that it also plays a key role in structuring predator assemblages.…”
Section: Discussionmentioning
confidence: 86%
“…Of the information necessary for conservation strategies, worldwide current species inventories and distributions are incomplete 111 . Further, data-poor locations inhibit the ability to monitor and record range extensions and distributional records.…”
Section: Discussionmentioning
confidence: 99%